Serum concentration of selected angiogenesis-related molecules differs among molecular subtypes, body mass index and menopausal status in breast cancer patients - Balalis, Dimitrios; Tsakogiannis, Dimitrios; Kalogera, Eleni; Kokkali, Stefania; Tripodaki, Elli; Ardavanis, Alexandros; Manatakis, Dimitrios; Dimas, Dionysios; Koufopoulos, Nektarios; Fostira, Florentia; Korkolis, Dimitrios; Misitzis, Ioannis; et al. (Journal of Clinical Medicine, 2022)
Background: Angiogenesis is a hallmark of breast cancer (BC) and is mediated by the vascular endothelial growth factor (VEGF) signaling axis. It is regulated by different proangiogenic factors, including platelet-derived growth factor-CC (PDGF-CC) and heparin-binding EGF-like growth factor (HB-EGF), as well as co-receptors, such as neuropilin-1, which could have prognostic implications in BC patients. Patients and methods: We assessed the serum levels of VEGF, HB-EGF, PDGF-CC and neuropilin-1 in 205 patients with early BC (invasive, n = 187; in situ, n = 18) and in 31 healthy donors (HD) and investigated the potential associations with clinical and histopathological parameters. Results: VEGF serum levels were significantly higher in patients with invasive versus ductal carcinomas in situ. PDGF-CC serum concentrations varied among BC molecular subtypes. Furthermore, we observed a differential expression of most biomarkers between overweight/obese (body mass index (BMI) ≥ 25 kg/m2) and non-obese patients among the BC molecular subtypes. Finally, the classification of subjects according to menopausal status revealed a significant difference in specific biomarker levels between patients and HD. Conclusion: The serum concentrations of angiogenic molecules differ among breast cancer molecular subtypes and are affected by the BMI and menopausal status, which could have possible clinical or prognostic implications.